Pengaruh Influencer Marketing pada Media Sosial Instagram terhadap Kepuasan Pembelian (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of influencer marketing on consumer purchase satisfaction on Instagram. The main focus is on influencer credibility, attractiveness, and consumer trust in product recommendations. This research uses a quantitative method through a survey involving 100 active Instagram users who have purchased products based on influencer recommendations. Data were analyzed using SmartPLS with stages including validity, reliability, regression, and structural model testing. The results indicate that both influencer marketing and consumer trust significantly affect purchase satisfaction, with consumer trust having a greater contribution. These findings reinforce the importance of building digital trust in influencer marketing strategies. The implication is that companies must carefully select credible and authentic influencers to enhance consumer satisfaction and loyalty through digital campaigns.